Articles Analysis Papers - Wagenaar, Theodore (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Summarize the article and discuss its relevance for what we covered in class or in the text. Include your reactions to the article. About three pages per summary, typed double spaced. Attach copies of the articles, unless they are in Sociology of Education, Sociological Quarterly, American Sociological Review, or Sociological Focus.